A non-target approach to identify disinfection byproducts of structurally similar sulfonamide antibiotics. (1st October 2016) - Wang, Mian; Helbling, Damian E.
Abstract: There is growing concern over the formation of new types of disinfection byproducts (DBPs) from pharmaceuticals and other emerging contaminants during drinking water production. Free chlorine is a widely used disinfectant that reacts non-selectively with organic molecules to form a variety of byproducts. In this research, we aimed to investigate the DBPs formed from three structurally similar sulfonamide antibiotics (sulfamethoxazole, sulfathiazole, and sulfadimethoxine) to determine how chemical structure influences the types of chlorination reactions observed. We conducted free chlorination experiments and developed a non-target approach to extract masses from the experimental dataset that represent the masses of candidate DBPs. Structures were assigned to the candidate DBPs based on analytical data and knowledge of chlorine chemistry. Confidence levels were assigned to each proposed structure according to conventions in the field. In total, 11, 12, and 15 DBP structures were proposed for sulfamethoxazole, sulfathiazole, and sulfadimethoxine, respectively. The structures of the products suggest a variety of reaction types including chlorine substitution, SC cleavage, SN hydrolysis, desulfonation, oxidation/hydroxylation, and conjugation reactions. Some reaction types were common to all of the sulfonamide antibiotics, but unique reaction types were also observed for each sulfonamide antibiotic suggesting that selective prediction of DBP structures of other sulfonamide antibiotics based on chemical structure is unlikely to be possible based on these data alone. This research offers an approach to comprehensively identify DBPs of organic molecules and fills in much needed data on the formation of specific DBPs from three environmentally relevant sulfonamide antibiotics. Graphical abstract: Highlights: High-resolution mass spectrometry to propose disinfection byproduct structures. Comprehensive identification of disinfection byproducts of pharmaceuticals. Structures of at least 11 disinfection byproducts proposed for each pharmaceutical. General reaction pathways identified to enable prediction of chlorine reactions.